ON THE SCIENTIFIC CONTRIBUTION OF A. AND KUKHTENKO TO DEVELOPMENT AIRCRAFT TECHNOLOGY - Fedorovsky, A. D. (Problems of Informatization and Management, 2021)
Simulators used to train cosmonauts of manned spacecraft are the main means of professional training of cosmonauts, since training flights into space are very expensive and dangerous. Beginning in 1968, the Arsenal plant began modeling, developing and manufacturing simulators for space simulators of the external visual environment observed by an astronaut, both in an optical device and in the windows of a manned spacecraft.